Development of a Core Set of Outcome Measures for Large-vessel Vasculitis: Report from OMERACT 2016 - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (My University, 2017)
Objective. Among the challenges in conducting clinical trials in large-vessel vasculitis (LVV), including both giant cell arteritis (GCA) and Takayasu arteritis (TA), is the lack of standardized and meaningful outcome measures. The Outcome Measures in Rheumatology (OMERACT) Vasculitis Working Group initiated an international effort to develop and validate data-driven outcome tools for clinical investigation in LVV. Methods. An international Delphi exercise was completed to gather opinions from clinical experts on LVV-related domains considered important to measure in trials. Patient interviews and focus groups were completed to identify outcomes of importance to patients. The results of these activities were presented and discussed in a “Virtual Special Interest Group” using telephone- and Internet-based conferences, discussions through electronic mail, and an in-person session at the 2016 OMERACT meeting. A preliminary core set of domains common for all forms of LVV with disease-specific elements was proposed. Results. The majority of experts agree with using common outcome measures for GCA and TA, with the option of supplementation with disease-specific items. Following interviews and focus groups, pain, fatigue, and emotional effect emerged as health-related quality of life domains important to patients. Current disease assessment tools, including the Birmingham Vasculitis Activity Score, were found to be inadequate to assess disease activity in GCA and standardized assessment of imaging tests were felt crucial to study LVV, especially TA. Conclusion. Initial data from a clinician Delphi exercise and structured patient interviews have provided themes toward an OMERACT-endorsed core set of domains and outcome measures.
Development of a Core Set of Outcome Measures for Large-vessel Vasculitis